2000
DOI: 10.1051/lait:2000114
|View full text |Cite
|
Sign up to set email alerts
|

Critical stability conditions in skimmed milk crossflow microfiltration: impact on operating modes

Abstract: diameter. During skimmed milk MF the fouling, mainly due to a deposit of casein micelles at the membrane surface, is dependent on a critical permeation flux, Jcrit, to wall shear stress, τ w ratio [2, 5]. Under this critical ratio the performance (permeability 1. INTRODUCTION Separation and concentration of casein micelles from soluble proteins of skimmed milk can be achieved by crossflow microfiltration, MF, using a 0.1 µm mean pore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 6 publications
2
32
0
Order By: Relevance
“…They showed that above the "critical" flux a significant hysteresis occurred but the deviation from linearity was not made clear. The stepwise filtration procedure has been commonly used to determine "critical" filtration conditions for a variety of fluids eg Gesan-Guiziou et al [19] , Kwon et al [20] , Manttari et al [21]. An identical step-by-step procedure but regulated on the permeate flux was used by Wu et al [10].…”
Section: Flux Stepping and Flux Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that above the "critical" flux a significant hysteresis occurred but the deviation from linearity was not made clear. The stepwise filtration procedure has been commonly used to determine "critical" filtration conditions for a variety of fluids eg Gesan-Guiziou et al [19] , Kwon et al [20] , Manttari et al [21]. An identical step-by-step procedure but regulated on the permeate flux was used by Wu et al [10].…”
Section: Flux Stepping and Flux Cyclingmentioning
confidence: 99%
“…• Gold sol : Madaeni [31] • Silica particles : [10] , [18] , Huisman et al [32] • Latex : [14] , [19] , [20] , [24] , Li et al [25] , [23] , Espinasse [33] , Kwon et al [34] , Vigneswaran et al [35] • Clays : Bacchin et al [30] , Cabassud et al [36] , Hamachi et al [37] , Kwon et al [38] Macromolecular solution • Proteins…”
Section: Colloidal Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing pressures and feed flow rates too can be beneficial. The critical flux concept (Gesan-Guiziou et al 2000), in which permeate flux is maintained at a level below that at which fouling occurs, is a promising idea, which has been demonstrated with milk (Youravong et al, 2003). Backflushing of some permeate into the retentate stream at intervals is a well-established method of clearing blocked pores and hence recovering flux during MF.…”
Section: Future Developmentsmentioning
confidence: 99%
“…The precise mechanisms for these observations are dependent on the fluid-particle-medium system and the prevailing hydrodynamic conditions. In the practical operation of filter systems, pressure difference measurements are commonly used to stop filter runs before the onset of breakthrough [18], but it has been suggested that for some filtration systems, wall shear stress measurements show better correlation with filter performance [10].…”
Section: Introductionmentioning
confidence: 99%